PEMANFAATAN TUMBUHAN OBAT OLEH SUKU DAYAK KANAYATN DI DESA MAMEK KECAMATAN MENYUKE KABUPATEN LANDAK - Riadi, Richi; Oramahi, H A; Yusro, Fathul (Universitas Tanjungpura, 2019)
Mamek village of Menyuke district of Landak Regency is one of the villages with Dayak Kanatytn as its majority ethnic and they still use medicinal plants. The aims of this research were to catalogue the medicinal plants and its utilization pattern of Dayak Kanaytn in Mamek village. Data were collected by interviews the selected respondents through questionnaire.Â The purposive sampling method was carried out and as much as 20% of total households of Mamek village was selected. There were 40 species of medicinal plants belongs to 31 plants family were used by Dayak Kanatyn in Mamek village. Types of medicinal plants based on leaf parts (18 plants species or 45%), decoction is the most common preparation method (32 species or 80%), oral is the most administration method (72%), home yard is the most plants sources location (17 species or 42,5%), and cultivated is the most cultivation method (35 species or 87,5%). The highest use value (UV) derived from sambung nyawa (Gymnathemum amygdalinum) (0.63). The highest informant consensus factor (ICF) with value 1 were obtained from diseases such as blood vomit, internal wound, swollen, sore, diarrhea, hepatitis, jaundice, measles, body odor, menstruation, urolitiasis, urinary tract infection, asthma, typhus, diabetic, mouthwash, digestion and palpitation. The highest fidelity level (FL) is 100% and value derived from alangÂ karue (Imperata Cylindrica), bawang merah (Allium cepa), bawang putih (Allium sativum), landep (Barleria prionitis), lengkuas (Alpinia galangal), bunga perujan (Ixora stricta roxb), ceri (Prunus avium), daun kesum (Polygonum minus), pepaya (Carica papaya), kedondong (Spondias dulcis forst), timun (Cucumis sativus), kelapa kuning (Cocos nucifera), mahkota dewa (Phaleria macrocarpa), pandan wangi (Pandanus amaryllifolius), puring (Codiaeum variegatum), lokop (Physalis peruviana) dengan nilai 100%.Keywords: Dayak Kanayatn, Medicinal Plants, Mamek Village